Everyday Sacred: Religion in Contemporary Quebec, edited by Hillary Kaell. - Palmer, Susan J. (International journal for the study of new religions, 2019)
Everyday Sacred: Religion in Contemporary Quebec, edited by Hillary Kaell. McGill-Queen’s University Press, 2017. 368pp., Pb. CDN$32.95, ISBN-13: 9780773550957.